The Impact of Brand Equity on the Consumers’ Purchase Intention: A Case of Uniqlo in Indonesia - Tjondrodihardjo, Jesslyn (iBuss Management, 2019)
In recent years, fashion industry has become one of the important sectors in Indonesia. Therefore, the competition in it which involves brands like Zara, H&M, and Forever 21 rushes to dominate Indonesia’s market. The higher competition in the industry forces Uniqlo to strengthen its position by building its brand equity, which can trigger the customer’s purchase intention. Thus, this research aims to analyse the impact of brand equity on purchase intention of Uniqlo’s products. This research will analyse the conceptualization of brand equity adopted from Aaker, which consists of brand awareness, brand association, perceived quality and brand loyalty.One hundred thirty three samples of Uniqlo customers domiciled in Indonesia are used in this research. Those samples are analysed using multiple regression analysis. The result shows perceived quality and brand loyalty significantly influence customer’s purchase intention of Uniqlo’s products. However, brand awareness and brand association are not significant in influencing customer’s purchase intention. Keyword: Brand Equity, Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty, Purchase Intention